Study the field of view influence on the monchromatic and polychromatic image quality of a human eye - Qasim, Adeeb Mansoor; Aljanabi, Mohammad; Shahreen, Kasim; Mohd Arfian, Ismail; Gusman, Taufik (Politeknik Negeri Padang, 2022)
In this paper, the effect of the eye field of view (known as F.O.V.) on the performance and quality of the image of the human eye is studied, analyzed, and presented in detail. The image quality of the retinal is numerically analyzed using the eye model of Liou and Brennan with this polymer contact lens. The images in digital form were collected from various sources such as photos, text structure, manuscripts, and graphics. These images were obtained from scanned documents or a scene. The color fringing, chromatic aberration addition to polychromatic effect was studied and analyzed. The Point Spreads Function (known as PSF) and The Modulation Transfers Function (known as MTF) were measured as the most appropriate measure of image quality. The calculations of the image quality were made by using Zemax software. Then, the calculation results demonstrate the value of correcting the chromatic aberration. The results presented in this paper showed that the image's form is so precise to the eye (F.O.V.). The image quality is degraded as (F.O.V.) increases due to the increment in spherical aberration and distortion aberration, respectively. In conclusion, the Zemax software used in this study assists the researcher's potential to design the human eye and correct the aberration by using external optics.